Modeling and simulation of 2D lithium‐ion solid state battery. (14th May 2015) - Bates, Alex; Mukherjee, Santanu; Schuppert, Nicholas; Son, Byungrak; Kim, Joo Gon; Park, Sam
Summary The goal of the work presented here was to develop a simulation approach for studying the effects of materials and geometry on the performance of Li‐ion Solid State Batteries (SSB). Simulation provides the opportunity to explore, with ease, different material properties and cell geometries to optimize a Li‐ion SSB's performance. Simulations shown in this paper are time‐dependent and consider electrochemical reaction, heat transfer, the diffusion of Li‐ions and electrons in the electrolyte, and solid Li diffusion in the positive electrode. A 2D model was simulated and the results shown. The simulations were able to show discharge curves, heat flux, the concentration of Li‐ions, electrons, and solid Li at any time in the discharge cycle. Copyright © 2015 John Wiley & Sons, Ltd.